Exploring the development of emissions from the heavy industry in Iceland using system dynamics - Kara Magnúsdóttir 1995- (2022)
The heavy industry is under immense pressure to reduce emissions and is transitioning towards a low-carbon future. In order to decarbonize, road maps and a holistic picture of the system are needed. In this thesis, system dynamics is used to analyze the heavy industry in Iceland to identify key variables in terms of emissions and look at what technological mitigation is available for the aluminum, ferrosilicon, and silicon industry. The thesis aims to examine the heavy industry in Iceland and look at it from all angles in terms of behavior and feedback mechanisms. The methods employed in this thesis are those of system analysis and system dynamics, which were built on the foundation of prior reviewed literature on the heavy industry related to current processes and technological mitigation. A simulation model was also developed to estimate CO2e emissions from the heavy industry in Iceland. Subsequently, a sensitivity analysis was conducted to analyze how technological solutions would affect the system. Formulating flow charts and CLDs demonstrated that the heavy industry's system is complex, and many influencing variables come into play. The system's structure was established by looking at how variables behaved, connected, and showed feedback. Consequently, simulation model results imply that emissions are projected to increase to 1.850 kt CO2e by 2040 if current processes and the best available technology are utilized. The results indicate that bio-carbon is favorable in the production of ferrosilicon and silicon along with utilizing CCS. In the case of the aluminum industry, implementing inert anodes into the aluminum smelting process may eliminate CO2e emissions, reduce cost, and decrease manual labor. However, some risk is associated with the technology, as it disrupts the production process, and technical issues can arise. Therefore, it should be implemented concurrently with the CCS technology. Stóriðjan stendur frammi fyrir miklum þrýstingi að draga úr losun og umskipti í átt að lágkolefnis framtíð eru ...